Fenomena Terbentuknya Komunitas Online Penggemar Drama Boys Love Thailand di Aplikasi Whatsapp Group (WAG) “Raikan” - Sari, Aslita; Yusuf, Yusmar (Dinasti Research, 2025)
This study was conducted to determine the origin of the online community of Thailand boys love drama fans in the whatsapp group (WAG) “Raikan”, to find out what is behind the online community members in the whatsapp group (WAG) “Raikan” like Thailand boys love drama, and to describe the factors that cause the popular culture of Thailand boys love drama to continue to grow and become more popular in Indonesia. The method used in this research is a qualitative research method using data collection techniques obtained through participant observation, interviews, documentation, and document studies using data analysis techniques in the form of coding (marking phenomena), noting (recording data), abstracting and comparing (interpreting and identifying), chacking and regfinement (rechecking), generalizing (preliminary conclusions), and theorizing (final conclusions and aligning data with the theoretical framework). The theory used in this research is Cyber Community theory. The results of this study show that the origin of the formation of the online community of Thailand boys love drama fans in the WhatsApp group (WAG) Raikan application is due to the desire to communicate and share information between fans and avoid interference from people who oppose boys love drama as a form of LGBT content. The background of the fans liking Thai boys love drama is curiosity, interesting storylines and handsome actors, bored with menotonous dramas, dislike of weak female characters in most dramas, and men as sexual objects.